EFFECT OF SPERMS FREEZABILITY ON SOME SEMEN ATTRIBUTES AND AMINO ACID CONCENTRATIONS IN SEMINAL PLASMA OF HOLSTEIN BULLS - T. A. Abdulkareem,; R. I. Khalil,; M. A. O. Al-Ezzi, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study investigated the effect of different sperm freezability on some semen characteristics and amino acid concentrations in the seminal plasma of Holstein bulls cryopreserved for two years. The semen straws (0.25 ml) that cryopreserved for two years were divided into three equal groups (7 bulls per group) according to the sperm’s freezability: medium (73.02%; F1), good (83.76%; F2), and high (91.20%; F3). The F1 bulls were superior (P≤ 0.05) in sperm’s cell individual motility (SCIM) for fresh semen as compared with F2 and F3 bulls. The F2 and F3 groups were superior (P≤ 0.01) to the F1 group in live sperm percentage at cryopreservation. The sperm’s DNA damage percentage was lesser (P≤ 0.05) in the F1 and F3 groups as compared with the F2 group. The differences among groups in normal sperm percentage, sperm’s plasma membrane and acrosome integrity percentage, malondialdehyde, and total antioxidant concentrations lacked significance. The essential and non-essential amino acid concentrations in seminal plasma did not differ among groups. In conclusion, sperm freezability influenced some semen attributes but did not affect amino acid concentrations in the seminal plasma of Holstein bulls.